PROSPECTIVE OPPORTUNITIES FOR THE DEVELOPMENT OF TRAVEL AGENCIES IN UKRAINE - MOLOZHNYKOVA, VIKTORIIA; MOHYLOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
For today tourism is one of the most profitable areas of the domestic economy, which has the potential for further development. In order for domestic tourism enterprises to achieve high efficiency in their activities, it is necessary to take various measures to increase the competitiveness of the company and make the most of the market opportunities available to the enterprise. The importance of analysis and assessment of market opportunities of the tourist enterprise is due to the fact that it is the key to effective activity in the market of tourism, maximum satisfaction of consumer needs and ensuring the commercial success of the firm. To strengthen the competitive position of any travel company needs to identify and assess market opportunities and use the most promising of them in future activities. This article examines the retrospective development and current trends in the market of tourist services in Ukraine. To identify obstacles that are a weakness of the development of the market of tourist services in Ukraine, the study conducted a survey of consumers on the current state of tourism in Ukraine and the further development of this area. The analysis of factors of competitiveness of travel agencies in Ukraine is carried out. Favorable market opportunities for travel agencies have been identified and assessed. Recommendations for improving the efficiency of the travel agency, finding the latest approach to the formation of its strong competitive position. The study proved that the opening of new tourist destinations (expanding the range of tours of the company) will allow tourism companies to increase the number of orders for international tours, and, as a result, to increase competitiveness at the regional level and make the most of its development. The implementation of the proposed recommendation measures in the practice of domestic enterprises in the market of tourist services will allow it to make the most of existing market opportunities, even in today’s crisis and to unleash the potential of its development.